The effect of tonsillectomy on the immune system: A systematic review and meta-analysis. Issue 8 (August 2015) - Bitar, Mohamad A.; Dowli, Alexander; Mourad, Marc
Abstract Importance The immunological sequelae of tonsillectomy in children have been a source of debate among physicians and a continuous concern for parents. Contradictory pertinent results exist in the literature. Objective To understand the real effect of tonsillectomy on the immune system. Data sources MEDLINE, EMBASE and COCHRANE. Study selection Articles addressing the effect of tonsillectomy on the immune system, up to Dec 2014. Related keywords and medical subject headings were used during the search. The abstracts were reviewed to determine suitability for inclusion based on a set of criteria. Manual crosscheck of references was performed. Data extraction We checked the tests results and the conclusion of each study to classify it as supporting or refuting the hypothesis of a negative effect of tonsillectomy on the immune system. Results We reviewed 35 articles, published between 1971 and 2014, including 1997 patients. Only Four studies (11.4%), including 406 patients (20.3%) found that tonsillectomy negatively affects the immune system. We performed a separate meta-analysis on various reviewed humoral and cellular immunological parameters (e.g. total and specific serum Ig's, SecIgA, cellular immunity, and Ag specific Ig). There is more evidence to suggest that tonsillectomy has no negative clinical or immunological sequalae on the immune system. Study limitations included heterogeneity in the diagnostic tools, timing of testing, indication for tonsillectomy and patients' age. Conclusion It is reasonable to say that there is enough evidence to conclude that tonsillectomy has no clinically significant negative effect on the immune system. It will be important for future studies to uniformly use both preoperative and control laboratory tests' levels to compare the postoperative levels with, to have short and long term follow-up levels, and to include both humoral and cellular immunity in their measurements. Relevance The results should reassure both surgeons and parents that tonsillectomy has no proven clinical sequalae. If more research is to be done in the future, it should be performed in a standardized way to avoid the heterogeneity seen in the literature.